Kautilya - The art of governance - Mathur, B.P. (2008)
Kautilya possessed remarkable insight in the art of statecraft and the general philosophy advocated by him is still relevant, more than two millennium after it was propounded. Kautilya was the first political theorist to realise the importance of wealth as the foundation of a strong and righteous State. Kautilya observed that the welfare and protection of the people is the main function of the King (Ruler) and it is through dandaniti - science of law enforcement, that the State secures its legitimacy and its right to govern. - Reproduced.
Keywords: Public administration